Optimizing Integrated Patient Progress Notes through the Application of Electronic Medical Record to Improve the Quality of Health Services: a Narrative Review - Nadi, Danu Tirta; Fortunandha, Dhea Keyle (Procedia of Engineering and Life Science, 2024)
Background: The completeness and accuracy of Integrated Patient Progress Notes (CPPT) are crucial for effective communication among healthcare professionals and safeguarding patient safety. However, Indonesian hospitals face significant challenges in achieving complete and accurate CPPTs, leading to risks such as medication errors. Objective: This study aims to identify the practices and challenges of CPPT in Indonesia through a narrative literature review and explore best practices from hospitals in various countries, focusing on the implementation of integrated patient progress note systems and the application of the Plan-Do-Study-Act (PDSA) quality improvement model. Method: The methodology used in this study is a narrative review concerning the usage, effectiveness, and issues faced by hospitals in implementing CPPT. Result: The narrative review reveals several barriers to CPPT completeness in Indonesia, including insufficient management commitment, limited healthcare personnel capacity, and inadequate infrastructure. An Ishikawa diagram was used to categorize these barriers. To address these issues, the study conducted benchmarking with international best practices, highlighting innovations such as the digitalization of CPPTs through Electronic Medical Records (EMR). Using the PDSA model, the study proposes a structured approach to digitalizing the CPPT process. The "Plan" phase identified key areas for improvement, the "Do" phase involved pilot implementation of digital CPPTs, the "Study" phase assessed the outcomes, and the "Act" phase provided recommendations for broader implementation. Conclusion: This study concludes that the digitalization of CPPTs is essential for improving patient safety and healthcare quality in Indonesia, aligning with national health regulations and international best practices.